2017
DOI: 10.1111/mcn.12538
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery and anaemia risk in children in 45 low‐ and middle‐income countries

Abstract: Caesarean delivery (CD) may reduce placental transfusion and cause poor iron-related haematological indices in the neonate. We aimed to explore the association between CD and anaemia in children aged <5 years utilising data from Demographic and Health Surveys conducted between 2005 and 2015 in 45 low- and middle-income countries (N = 132,877). We defined anaemia categories based on haemoglobin levels, analysed each country's data separately using propensity-score weighting, pooled the country-specific odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
1
Order By: Relevance
“…Delivery via cesarean section (C-section) was also associated with significantly lower haemoglobin among the sample. This contrasts with other previous studies, which have found no significant associations between C-section births and anaemia among infants and toddlers in China and in LMICs more generally (23,36) . However, one study by Li et al did find C-section to be associated with anaemia at 12 months and 58 months of age (37) .…”
Section: Discussioncontrasting
confidence: 99%
“…Delivery via cesarean section (C-section) was also associated with significantly lower haemoglobin among the sample. This contrasts with other previous studies, which have found no significant associations between C-section births and anaemia among infants and toddlers in China and in LMICs more generally (23,36) . However, one study by Li et al did find C-section to be associated with anaemia at 12 months and 58 months of age (37) .…”
Section: Discussioncontrasting
confidence: 99%